The handbook of institutional research - Howard, Richard D.; McLaughlin, Gerald W.; Knight, William E., 1965- (Jossey-Bass higher and adult education series., 2012)
"As the demand for accountability grows, institutions are under pressure to improve their ability to report a wide variety of data to various stakeholders. The Handbook of Institutional Research offers institutional researchers and all college and university administrators the most current and comprehensive overview of theory and practice in the field. The volume covers the areas of research as well as methodologies, tools, and techniques. The book covers topics including The History, Practice, and Theory of Institutional Research; Institutional Research Support of Institutional Functions; Building and Using External and Internal Data Sources; and Institutional Research Tools and Techniques"--